1995
DOI: 10.1007/bf03401892
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Macrophage Migration Inhibitory Factor (MIF) to Secretory Granules within the Corticotrophic and Thyrotrophic Cells of the Pituitary Gland

Abstract: Background: Macrophage migration inhibitory factor (MIF) was one of the first lymphokine activities to be discovered and was described almost 30 years ago to be a soluble factor(s) produced by activated T lymphocytes. In more recent studies, MIF has been "rediscovered" to be an abundant, pre-formed constituent of the anterior pituitary gland and the macrophage, and to be a critical component in the host response to septic shock. Pituitary-derived MIF enters the circulation after infectious or stressful stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
132
1
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(140 citation statements)
references
References 14 publications
6
132
1
1
Order By: Relevance
“…36 Of note, the anterior pituitary gland has been shown to be an important source of MIF in rodents, 3 and secretes MIF in response to physiological or infective stress. 37,38 While there is some evidence that the hypothalamic-pituitary-adrenal (HPA) axis may play a role in the pathogenesis of rheumatoid arthritis in certain patients, 39 MIF does not appear to colocalize in the pituitary gland with the known expression pattern of Pit-1. 36,38,40 Since the initiation of these studies, a −173*G/C single nucleotide polymorphism (SNP) in the Mif gene promoter has been reported by Donn et al 41 and was shown to be associated with systemic-onset juvenile idiopathic arthritis (systemic-onset JIA).…”
Section: Discussionmentioning
confidence: 99%
“…36 Of note, the anterior pituitary gland has been shown to be an important source of MIF in rodents, 3 and secretes MIF in response to physiological or infective stress. 37,38 While there is some evidence that the hypothalamic-pituitary-adrenal (HPA) axis may play a role in the pathogenesis of rheumatoid arthritis in certain patients, 39 MIF does not appear to colocalize in the pituitary gland with the known expression pattern of Pit-1. 36,38,40 Since the initiation of these studies, a −173*G/C single nucleotide polymorphism (SNP) in the Mif gene promoter has been reported by Donn et al 41 and was shown to be associated with systemic-onset juvenile idiopathic arthritis (systemic-onset JIA).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified MIF to be a new pituitary peptide that colocalizes to the ACTH and TSH secretory granules of the corticotrophic and thyrotrophic cells (3,5). MIF is released from the pituitary gland upon activation of the hypothalamic-pituitary-adrenal axis and contributes to the increase in the serum concentration of MIF during endotoxemia and stress (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…A much broader role for MIF has recently emerged from studies that have identified this protein to be an abundant preformed constituent of the anterior pituitary gland and of monocytes͞macrophages (3,4). MIF is colocalized with corticotropin (ACTH) and thyroid stimulating hormone (TSH) in the secretory granules of corticotrophic and thyrotrophic cells of the pituitary gland and is released into the bloodstream in response to various proinflammatory stimuli (5). MIF plays a pivotal role in the host response to endotoxic shock, and the administration of neutralizing anti-MIF antibodies fully protects animals from lethal endotoxemia (3).…”
mentioning
confidence: 99%
“…Among the soluble mediators regulating the expression of these molecules is a 12.5-kDa protein known as macrophage migration inhibitory factor (MIF). MIF was one of the first cytokines described, and is secreted by activated T cells, macrophages, and a variety of nonimmune cells (7)(8)(9)(10). MIF was recently cloned and shown to have a plethora of immunologic activities, including the inhibition of migration and enhanced TNF-␣ and NO production by macrophages (11,12).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%